ANALISIS DAN STRATEGI KINERJA PERBANKAN SYARIAH DALAM MEDONGKRAK PEREKONOMIAN INDONESIA - Febrianto, Gustaf Naufan (Gapenas Publisher, 2024)
This research aims to analyze and provide strategies for Sharia banking performance in boosting the Indonesian economy. This research uses a quantitative approach with a population of four Islamic banking companies registered on the IDX, which were selected using a purposive sampling method. Data obtained from www.idx.co.id, www.bps.go.id, and www.bi.go.id. The data analysis technique uses multiple linear regression with the help of SPSS 25 software and a significance level of 5%. The research results show that simultaneously, macroeconomics (X1), capital (X2), and GCG (X3) do not have a significant effect on company profitability. Partially, macroeconomics (X1) and GCG (X3) also do not have a significant effect on company profitability. However, the capital variable (X2) has a significant influence on company profitability. Future researchers can add a research period, because there is only one variable that has a significant influence, and can add other factors that influence company profitability, apart from the variables contained in this research and provide strategies to boost the Indonesian economy